2021
DOI: 10.1130/g48894.1
|View full text |Cite
|
Sign up to set email alerts
|

Central eastern China hydrological changes and ENSO-like variability over the past 1800 yr

Abstract: Variations in East Asian summer monsoon (EASM) precipitation impact agriculture, water resources, electricity generation, and economic development in the densely populated region of central eastern China. However, uncertainties remain in the history and driving mechanisms of precipitation changes in this region over the past two millennia. We present an 1800 yr multiproxy reconstruction of monsoon precipitation based on hydroclimate variations inferred from Lake Nvshan sediments in the Jiang-Huai region of cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…The ENSO‐like SST anomaly in the tropical Pacific Ocean influences the strength and position of the WNPSH (Chang et al., 2000; B. Wang et al., 2000), which further directs monsoonal moisture to (away from) north and northwest China during La Niña (El Niño) phase from (to) central eastern China (Z. Liu et al., 2016; Yuan et al., 2020). Such mechanism finds the support in the existence of the general anti‐phasing between Ngoring Lake records and newly retrieved precipitation records from Nvshan Lake in central eastern China (Jiang et al., 2021) (Figure 3). Additionally, the development of an anomalous barotropic cyclone over East Asia (Wu et al., 2003), the westward Rossby wave (C. Li & Zeng, 2013), and the western Tibetan Plateau snow cover (Jin et al., 2018) have also been demonstrated by simulation and reanalysis studies as linkages between the tropical Pacific and the precipitation changes in north/northwest China or the Yellow River basin.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The ENSO‐like SST anomaly in the tropical Pacific Ocean influences the strength and position of the WNPSH (Chang et al., 2000; B. Wang et al., 2000), which further directs monsoonal moisture to (away from) north and northwest China during La Niña (El Niño) phase from (to) central eastern China (Z. Liu et al., 2016; Yuan et al., 2020). Such mechanism finds the support in the existence of the general anti‐phasing between Ngoring Lake records and newly retrieved precipitation records from Nvshan Lake in central eastern China (Jiang et al., 2021) (Figure 3). Additionally, the development of an anomalous barotropic cyclone over East Asia (Wu et al., 2003), the westward Rossby wave (C. Li & Zeng, 2013), and the western Tibetan Plateau snow cover (Jin et al., 2018) have also been demonstrated by simulation and reanalysis studies as linkages between the tropical Pacific and the precipitation changes in north/northwest China or the Yellow River basin.…”
Section: Discussionmentioning
confidence: 58%
“… Ngoring Lake carbonate content record in comparison with regional precipitation records and the tropical Pacific sea surface temperature (SST) records: (a) Indo Pacific Warm Pool (IPWP) SST (purple) reconstructed from sediment cores from the Makassar Strait (Oppo et al., 2009) and eastern equatorial Pacific (EEP) SST (pink) reconstructed from El Junco Lake diatom record (Conroy et al., 2009); (b) Tropical Pacific zonal SST gradient, calculated from the data in (a) (Conroy et al., 2010); (c) simulated north China precipitation change (light blue) from the MPI‐ESM model (Xu et al., 2020) and annual precipitation (light green) reconstructed from Gonghai Lake pollen record (Chen et al., 2015); (d) Ngoring Lake carbonate content record (this study); (e) Nvshan Lake core NSH sediment a*/L* record (Jiang et al., 2021) (a*/L* is a parameter to describe the redness of sediment). The light blue shading indicates a near‐millennium‐long drought trend inferred from carbonate content record.…”
Section: Discussionmentioning
confidence: 87%
“…6k,l) (Leduc et al 2007, Stott et al 2004. Previous studies suggested that an increasing ENSO would strengthen the WPSH along with the eastward migration of warm water in the Tropical Pacific (Hong et al 2001, Lu et al 2018, and force the WPSH to move southwestwards (Chen et al 2015b, Huang et al 2012, resulting in more precipitation in the middle and lower Yangtze River catchment and less precipitation in northern China (Jiang et al 2021, Xie et al 2013. However, during the period of potentially enhanced WPSH associated with an increasing ENSO from 2300 to 600 cal a BP, the Kuroshio Current originating from the North Equatorial Current (NEC) intensified, as indicated by an increasing amount of planktonic foraminifera in the Okinawa Trough (Fig.…”
Section: Possible Forcing Mechanisms Of the Anti-phase Relationshipmentioning
confidence: 99%
“…In addition, it is widely recognized that the EASM intensity was different from the EASM precipitation in some EASM subregions. For example, a weakening/strengthening of the EASM during the LIA/MWP could cause increased/decreased precipitation in the middle and lower Yangtze River catchment (Jiang et al 2021, Zhang et al 2021c) and parts of southern China (e.g. Chu et al 2002), constituting a sandwich pattern or a dipole mode of the EASM precipitation in eastern China (e.g.…”
Section: Comparison With Paleoclimatic Records In the Easm Regionmentioning
confidence: 99%
See 1 more Smart Citation